Analisis Sentimen Masyarakat Mengenai RUU Perampasan Aset Di Twitter Menggunakan Metode NaÃ¯ve Bayes - kivandi Nugroho; Firman Noor Hasan (SMATIKA JURNAL : STIKI Informatika Jurnal, 2023)
The development of the world is growing especially in social media, one of which is Twitter. Twitter itself is a social media that can be accessed by various groups to communicate, besides that there are various kinds of public opinions that are quite varied. Data collection from Twitter can be used to conduct sentiment analysis in order to find out public opinion. The research conducted by researchers is an analysis of public sentiment regarding RUU Perampasan Aset that has never been passed. This research starts from data collection, processing, data implementation and evaluation using rapidminer tools. In the data retrieval process, researchers used the keyword "RUU Perampasan Aset", the data that was successfully obtained was 413, which was then processed at the Preprocessing stage so that later it could be analyzed using the naÃ¯ve bayes method in this process 179 data were obtained. The results obtained in the form of positive and negative analysis of RUU Perampasan Asetl, obtained as many as 131 or 73% positive comments and only 48 or 27% negative comments. For positive class precision 90%, and class recall of 55%, while for negative class precision 42%, and class recall of 85%, with accuracy obtained at 63%.